Comparison of Continuing Bonds Reported by Parents and Siblings After a Child's Death from Cancer - Foster, Terrah L. (2011)
Few studies have distinguished similarities and differences between continuing bonds as they appear in various bereaved populations, particularly parent versus sibling cohorts following a child's death. This mixed-method study compared how parents and siblings experienced continuing bonds in 40 families who lost a child to cancer. Thirty-six mothers, 24 fathers, and 39 siblings were recruited 3-12 months post-loss (M = 10.7, SD = 3.5). Nearly all participants (97%) reported engaging in purposeful bonds with deceased children, while only 14% reported nonpurposeful connections. Over half of participants (58%) experienced comforting effects from reminders of the deceased child, while only 10% of family members experienced discomforting effects. Mothers communicated with the deceased, thought about the deceased, and did things that the deceased child would have liked more often than siblings. Mothers also reported significantly more comforting effects than siblings. Additional research is needed to further delineate continuing bonds for different types of loss and examine associations with positive and negative outcomes for bereaved individuals.